Dynamics of Mechanical Systems - Ross, C. T. F., 1935- (Horwood Pub., 1997)
Adopting a step by step methodical approach, the book is aimed at first and second year undergraduates and addresses the mathematical difficulties faced by them. Solution manual free from: http://www.mech.port.ac.uk/sdalby/mbm/CTFRSoln.htmAdopts a step-by-step methodical approach in explaining the dynamics of mechanical systemsAddresses the mathematical difficulties faced by first and second year undergraduates.